Mycorrhizas and soil ecosystem function of co-existing woody vegetation islands at the alpine tree line - Wang, Lixia; Otgonsuren, Burenjargal; Godbold, Douglas L (Plant and soil, 2017)
BACKGROUND AND AIMS: Picea abies, Pinus mugo and Rhododendron ferrugineum co-exist at the alpine tree line, and can have different mycorrhizal communities. The activity and diversity of mycorrhizal fungi are considered to be important factors in regulation of soil function. METHODS: At a tree line site and a lower elevation site in the Austrian Alps, the community structure of ectomycorrhiza on Picea abies and Pinus mugo was determined. The activity of surface enzymes was determined on ectomycorrhizal and ericoid mycorrhizal roots. In soils, the activity of a range of enzymes, nitrogen (N) mineralization and biomass decomposition were determined. RESULTS: The community structure of the ectomycorrhizal community of Picea abies and Pinus mugo differed strongly, but the average activity of surface enzymes of the ectomycorrhizal communities was similar. A lower root surface enzyme activity was determined on Rhododendron ferrugineum. Soil N-mineralization under Rhododendron ferrugineum was significantly lower than under Picea abies and Pinus mugo. In soil, the activity of a range of enzymes did not differ at the tree line but differed between the tree line and the lower elevation sites. CONCLUSION: The different ectomycorrhizal communities on Picea abies and Pinus mugo and ericoid mycorrhizas on Rhododendron ferrugineum support similar ecosystem functions in soil.
Keywords: Ectoenzymes; Ectomycorrhizas; Enzyme activity; Ericoid mycorrhizas; Nitrogen-mineralization